Penggunaan Berbagai Komposisi Media Tanam dan Konsentrasi Pupuk Organik Cair (POC) Terhadap Produksi Tanaman Sawi di Desa Mappesangka, Kec. Ponre, Kab. Bone, Provinsi Sulawesi Selatan - Abu Darwis, Andi Zulfiana; Budianto, Budianto; Muditha, I GD Nyoman (bionature, 2020)
Abstract. This study aims to determine the effect and prove the composition of the planting media and the concentration of liquid organic fertilizer that can provide growth and yield of mustard plants. The design used was a randomized block design (RCBD) with three replications. The first factor is the composition of the planting medium which is a mixture of soil, charcoal husk, and manure consisting of three compositions, namely 1: 2: 2, 2: 2: 1, 2: 1: 2. The second factor is the concentration of liquid organic fertilizer with a concentration of 2.5 ml / l, 5 ml / l, 7.5 ml / l. The results showed that the interaction between the use of the composition of the planting media and the concentration of liquid organic fertilizer was appropriate, namely a ratio of 1: 2: 2 and the concentration of liquid organic fertilizer of 7.5 ml / l significantly affected the observation parameters of leaf width, leaf length, and weight plant.Keywords: Growing media, liquid organic fertilizer, mustard plantÂ